Sedation for Colonoscopy: A Double-Blind Comparison of Diazepam/Meperidine, Midazolam/Fentanyl and Propofol/Fentanyl Combinations. (1st February 1994) - Kostash, Mark A; Johnston, Richard; Bailey, RJ; Konopad, Elsie M; Guthrie, Lorraine P
Abstract : Rate of recovery and incidence of complications were compared among three intravenous sedation techniques for colonoscopy. Sixty patients were randomized to receive diazepam and meperidine, midazolam and fentanyl, or propofol and fentanyl with a continuous infusion of propofol. Patients were sedated to a standard end-point using a double-blinded technique. There were no differences in rate of recovery or incidence of minor side effects among the three groups. The techniques were equally effective in providing sedation and analgesia for colonoscopy. All groups developed significant oxygen desaturation measured by continuous pulse oximetry. Over 20% of patients required supplemental oxygen due to persistent desaturation below 85% following administration of sedatives. The authors conclude that oxygen should be administered to all patients undergoing colonoscopy.